Characteristics, Biological Properties and Analytical Methods of Ursolic Acid: A Review - Pironi, Andressa Maria [UNESP]; de Araújo, Patricia Rocha [UNESP]; Fernandes, Mariza Aires [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2018)
Ursolic acid (UA) is a naturally occurring triterpenoid which is a promising candidate for the development of new therapeutic approaches and for the prevention and treatment of several diseases owing to its pharmacological importance. However, its low solubility in aqueous medium affects its therapeutic application. Several strategies have been used to overcome this obstacle. In this study, the incorporation of UA in to different drug delivery systems was found to be highly efficient. In addition, important investigations were performed about methods for qualitative and quantitative analyses of UA in various raw materials, including plants, biological fluids, and drug delivery systems, were investigated. Most recently high performance liquid chromatography coupled with various detectors, gas chromatography-mass spectrometry and capillary electrophoresis were used for this purpose. Thus, this review was performed to evaluate the biological effects of UA demonstrated thus far as well as the currently used, delivery systems and analytical methods.
Keywords: analytical methods; biological effects; drug delivery systems; Ursolic acid